National Collegiate Athletic Association coaches' beliefs toward seeking mental health services for themselves: instrument validation and exploratory investigation - Tolentino, K.; Raabe, J. (Journal of Clinical Psychology, 2025)
While the environment in which National Collegiate Athletic Association coaches operate makes them susceptible to mental health issues, many do not seek professional help. The Reasoned Action Approach posits that attitudes, perceived behavioral control, and perceived norms shape intentions for help-seeking behaviors. This study was designed to: (a) validate two commonly utilized instruments measuring psychological help-seeking beliefs for use with National Collegiate Athletic Association coaches; (b) assess coaches` attitudes, perceived behavioral control, and perceived norms toward seeking mental health services for themselves; and (c) examine differences in beliefs based on gender, race, coaching role, age, and coaching experience. N = 1,424 National Collegiate Athletic Association Division I, II, and III coaches participated. Confirmatory factor analyses indicated the Inventory of Attitudes Toward Seeking Mental Health Services provides valid and reliable measurements for participants` beliefs toward seeking services for themselves. Participants reported moderately positive attitudes, perceived behavioral control, and perceived norms. Male coaches indicated significantly lower positive beliefs than female coaches.